Faraid calculator (mobile application) / Shazwani Samsurim - Shazwani, Samsurim (2016)
Faraid Calculator was developed to help people especially Muslim in managing the properties of their deceased. The main objective of the development of this application is to overcome the problems exist in the current manual system. Smart phones are widely used today and can be used as platform to calculate the portions for each beneficiary. Based on the literature review, most of Faraid applications are on web, thus user need the internet connection to use the application. The main problem is not everyone has the internet connection. Therefore, Faraid Calculator will be developed as an offline android application to overcome the current problem. User can make the calculation by entering the right amount of properties of the deceased and then, the Faraid Calculator will automatically calculate the appropriate amount.